FEATURES OF THE INTESTINAL MICROBIOTA IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - L. M. Ogorodova; V. M. Govorun; S. V. Fedosenko; M. A. Karnaushkina; I. V. Saltykova; D. G. Alekseyev; Ye. S. Kostrytikova; A. V. Tyakht; A. S. Popenko (Бюллетень сибирской медицины)
The article summarizes the results of studies on the composition of microbial communities in stool samples of patients with chronic obstructive pulmonary disease (COPD) compared with healthy volunteers using genome-metagenomic sequencing. It is shown that the microbial community of the intestine in COPD patients is characterized as diverse taxonomic composition of metagenomes that the healthy volunteers microbiota. In this case, the normal composition of intestinal microbiota in patients with COPD is exposed to the qualitative and quantitative modifications. In contrast to healthy volunteers, the intestinal microbiota in patients with COPD is characterized by the presence of representatives of the Proteobacteria, as Citrobacter, Enterobacter, Eggerthella,Proteus, Salmonella, Anaerococcus, Clostridium difficile, Pseudomonas, as well as higher insemination fungus genusCandida (Candida dubliniensis and Candida albicans).